Voters’ Perceptions of Mayoral Candidates’ Personal Characteristics in the 2024 Bogor Mayoral Election - Aini, Febri Nur; Munanda, Jono Mintarto; Sumertajaya, I Made (Asian Journal of Social and Humanities, 2025)
This study examines voters’ perceptions of the personal characteristics of mayoral candidates in the 2024 Bogor mayoral election. Using survey data collected from voters, the analysis focuses on fifteen character attributes, including sociability, communication skills, decisiveness, trustworthiness, responsibility, integrity, and competence. Descriptive analysis was employed to compare positive and negative perceptions across five candidates. The results indicate that all candidates were perceived very positively across most attributes. Characteristics related to leadership and integrity—such as decisiveness, honesty, responsibility, intelligence, and consistency—received exceptionally high positive evaluations, reaching 100 percent for several candidates. Candidates with larger numbers of respondents exhibited more consistent and stable positive perceptions across all indicators. In contrast, candidates with fewer respondents showed relatively higher negative perceptions, particularly in communication-related attributes, suggesting variability in public image formation. Overall, the findings highlight the importance of personal character dimensions in shaping voter perceptions in local elections. Voters tend to favor candidates perceived as credible, competent, and emotionally stable, underscoring the role of character-based evaluations in influencing electoral preferences in the 2024 Bogor mayoral election.